2016
DOI: 10.1111/1440-1681.12595
|View full text |Cite
|
Sign up to set email alerts
|

Orchidectomy attenuates high‐salt diet‐induced increases in blood pressure, renovascular resistance, and hind limb vascular dysfunction: role of testosterone

Abstract: Sex hormone-dependent vascular reactivity is an underlying factor contributing to sex differences in salt-dependent hypertension. This study evaluated the role of androgens (testosterone) in high salt-induced increase in blood pressure (BP) and altered vascular reactivity in renal blood flow and perfused hind limb preparation. Weanling male rats (8 weeks old, 180-200 g) were bilaterally orchidectomised or sham operated with or without testosterone replacement (Sustanon 250, 10 mg/kg intramuscularly once in 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
(72 reference statements)
5
12
0
Order By: Relevance
“…Oloyo et al made similar observations in the abdominal aortic rings from SD rats fed a high-salt diet. 6,7 In line with the results of this study, in Dahl saltsensitive hypertensive rats, a high-salt diet was reported to impair endothelium-dependent relaxations induced by a variety of vasodilators. 19,20 This impairment could best be explained by reduced activity and expression of the eNOS mRNA which results in reduced conversion of the substrate, l-arginine present in the plasma to usable nitric oxide to cause vasodilation.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Oloyo et al made similar observations in the abdominal aortic rings from SD rats fed a high-salt diet. 6,7 In line with the results of this study, in Dahl saltsensitive hypertensive rats, a high-salt diet was reported to impair endothelium-dependent relaxations induced by a variety of vasodilators. 19,20 This impairment could best be explained by reduced activity and expression of the eNOS mRNA which results in reduced conversion of the substrate, l-arginine present in the plasma to usable nitric oxide to cause vasodilation.…”
Section: Discussionsupporting
confidence: 80%
“…[21][22][23] Also, previous studies have demonstrated clearly that vascular functions and more importantly endothelium-dependent relaxations are impaired following elevated dietary salt intake in animals and humans. 6,7,24 Many mechanisms have been proposed for this impairment part of which is failure of nitric oxide from the l-arginine-nitric oxide pathway in the endothelium to cause vasodilation 6,24 and alteration in eNOS gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, high-salt diet is a major risk factor for the pathogenesis and progression of hypertension in modern society (6). Accumulating evidence indicates that the mechanism of high salt-induced hypertension may include expanded blood volume, increased blood flow and, ultimately, hypertension (7). Furthermore, as numerous studies indicate, high dietary salt intake poses a threat to target organs, increasing the risk of early morbidity and mortality, in addition to its impact on blood pressure, and clinical data also confirm that multiple factors likely contribute to high salt-induced hypertension (2).…”
Section: Introductionmentioning
confidence: 99%